2011
DOI: 10.1155/2011/598148
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Current Role of Minimally Invasive Spine Surgery in the Management of Metastatic Spine Disease

Abstract: Although increasingly aggressive decompression and resection methods have resulted in improved outcomes for patients with metastatic spine disease, these aggressive surgeries are not feasible for patients with numerous comorbid conditions. Such patients stand to benefit from management via minimally invasive spine surgery (MIS), given its association with decreased perioperative morbidity. We performed a systematic review of literature with the goal of evaluating the clinical efficacy and safety of MIS in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 50 publications
2
48
0
Order By: Relevance
“…39 There have been technical reports and cadaver studies of MIS posterior-only corpectomies, but there are few clinical reports of utilizing the technique in the treatment for spinal metastasis. 36,40 Taghva et al re- ported the use of MIS via expandable tubular retractors in the treatment of a 36-year-old man with metastatic lung adenocarcinoma to the spine.…”
Section: Discussionmentioning
confidence: 99%
“…39 There have been technical reports and cadaver studies of MIS posterior-only corpectomies, but there are few clinical reports of utilizing the technique in the treatment for spinal metastasis. 36,40 Taghva et al re- ported the use of MIS via expandable tubular retractors in the treatment of a 36-year-old man with metastatic lung adenocarcinoma to the spine.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review of the literature, Molina et al 8 found only 11 publications that addressed minimally invasive surgery in the treatment of metastatic spine disease. Most of these publications were case reports or limited retrospective case series that reported the efficiency of video-assisted or minimally invasive anterior approaches.…”
Section: Clinical Efficiencymentioning
confidence: 99%
“…10 Longer hospital stays are indicative of increased patient morbidity. In the review of Molina et al, 8 decreased complication rates, blood loss, and length of hospital stay are believed to be among the benefits of minimally invasive approaches. These benefits were confirmed by our results when compared with gath-ered data outcomes for standard surgery.…”
Section: Morbidity and Complicationsmentioning
confidence: 99%
“…Similarly, our review of the VATS and MASS literature for anterior T and TLJ spinal reconstruction showed that VATS was more likely to need operating time and to increase blood loss. In addition, Molina et al [32], in a systematic review of MIS in the management of metastatic spine disease, reported that VATS was associated with longer operating time, a longer length of stay in the hospital, and more blood loss than was MASS. We found that since MASS seems more familiar to most surgeons it yields faster and safer decompression, stabilization, and reconstruction than does VATS.…”
Section: Discussionmentioning
confidence: 99%